Suxiao Jiuxin Pill attenuates acute myocardial ischemia via regulation of coronary artery tone - Li, Sa; Zhan, Jiaguo; Wang, Yucheng; Oduro, Patrick Kwabena; Owusu, Felix Boahen; Zhang, Jiale; Leng, Ling; Li, Ruiqiao; Wei, Shujie; He, Jun; Wang, Qilong (Frontiers in Pharmacology, 2023)
Suxiao Jiuxin Pill (SJP) is a well-known traditional Chinese medicine drug used to manage heart diseases. This study aimed at determining the pharmacological effects of SJP in acute myocardial infarction (AMI), and the molecular pathways its active compounds target to induce coronary artery vasorelaxation. Using the AMI rat model, SJP improved cardiac function and elevated ST segment. LC-MS and GC-MS detected twenty-eight non-volatile compounds and eleven volatile compounds in sera from SJP-treated rats. Network pharmacology analysis revealed eNOS and PTGS2 as the key drug targets. Indeed, SJP induced coronary artery relaxation via activation of the eNOS-NO pathway. Several of SJP's main compounds, like senkyunolide A, scopoletin, and borneol, caused concentration-dependent coronary artery relaxation. Senkyunolide A and scopoletin increased eNOS and Akt phosphorylation in human umbilical vein endothelial cells (HUVECs). Molecular docking and surface plasmon resonance (SPR) revealed an interaction between senkynolide A/scopoletin and Akt. Vasodilation caused by senkyunolide A and scopoletin was inhibited by uprosertib (Akt inhibitor) and eNOS/sGC/PKG axis inhibitors. This suggests that senkyunolide A and scopoletin relax coronary arteries through the Akt-eNOS-NO pathway. In addition, borneol induced endothelium-independent vasorelaxation of the coronary artery. The Kv channel inhibitor 4-AP, KCa2+ inhibitor TEA, and Kir inhibitor BaCl2 significantly inhibited the vasorelaxant effect of borneol in the coronary artery. In conclusion, the results show that Suxiao Jiuxin Pill protects the heart against acute myocardial infarction.